Idealisme, Love Of Money, dan Intensi untuk Melakukan Manajemen Laba dalam Skema Pemberian Bonus: Sebuah Pendekatan Eksperimen - I Putu Hendra Martadinata (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Earnings management is one of the deviant behavior of managers that is widely studied in behavioral research. Earnings management can be influenced by individual personal characteristics as well as external factors originating from the environment around the individual. This study aims to examine the effect of idealism and love of money on the intention to perform earnings management based on the manager's bonus scheme. This study is based on the findings of previous research which found a tendency for deviant behavior in individuals despite having high ethical ideals. This study suspects that financial motivation can change the ethical orientation of individuals so that they can fall into unethical decision making. This study uses an experimental method with a 2x1 between subject design. The bonus scheme was used as a treatment in the experiment. The participants consisted of 45 Master of Science in Accounting students and 57 Master of Accounting students from Gadjah Mada University, with a total of 102 participants. Hypothesis testing was carried out using the analysis of variance (ANOVA) method. The results of this study indicate that idealism weakens managers' intentions to perform earnings management, while love of money and variable bonus schemes strengthens managers' intentions to perform earnings management. When idealism, love of money, and bonus schemes are combined, the variable bonus scheme strengthens the intention to perform earnings management in managers with high love of money, regardless of the level of idealism. The results of this study indicate that the combination of personal characteristics and the performance reward system applied in the company can influence managers’ ethical decision making